POTENSI PEMANFAATAN LIMBAH PLASTIK SEBAGAI ALTERNATIF ELEMEN PENGGANTI DI BANGUNAN CAGAR BUDAYA KOTA SEMARANG (Studi Kasus: Soesman Kantoor) - Kurniasari, Frista; Hermawan, Ferry; Sudarno, Sudarno (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2020)
Indonesia as the second largest contributor in global were produced about 9.52 million tons plastic or 14% of the total waste. The rapid population growth of urban area in Indonesia indirectly encourages various activities that affect the volume of waste. Semarang city were contributing waste in landfills reaches 850,000 tons per day, where 1,000 tons unmanageable. Unsorted garbage has the potential as new materials option in cultural heritage buildings. To elaborate these potential options, this research has been conducted qualitative method as the best approach to answer the research question. This research investigates the stakeholders’ perspectives about potential of plastic waste for replacement material of heritage buildings. The results show that there is a lack of data on waste management which is one of the challenges to find out how much volume of plastic waste can be reused. In addition, the principle of building cultural heritage is opposed to the use of plastic waste as an alternative material as a substitute element. In conclusion, plastic waste has a little potential from current waste to be applied on heritage buildings are limited element such as roof, furniture or temporary support of the structural element.